The study of extended emission in a radio galaxy detected in the LOFAR Two-Metre Sky Survey. Issue 2 (7th February 2019) - Thwala, S A; Shafi, N; Colafrancesco, S; Govoni, F; Murgia, M
Abstract: We performed a search for extended radio sources in the Low-Frequency Array Two-Meter Survey HETDEX Spring Field, and we were able to identify 11 low-brightness extended sources. In this paper we focus on the poorly studied radio galaxy PGC2285791, presenting a detailed analysis of its core, its two extended radio lobes, a spectral index map between 141 and 1400 MHz, and the multifrequency association with its IR and optical counterparts. Our results led to the identification of this source with a z  = 0.14 extended radio galaxy exhibiting bubble-like radio lobe structures (∼6 arcmin in the S–N direction).